PPARgamma Pro12Ala Pro/Pro and resistin SNP-420 G/G genotypes are synergistically associated with plasma resistin in the Japanese general population - Osawa, Haruhiko; Tabara, Yasuharu; Kawamoto, Ryuichi; Ohashi, Jun; Ochi, Masaaki; Onuma, Hiroshi; Nishida, Wataru; Yamada, Kazuya; Nakura, Jun; Miki, Tetsuro; Makino, Hideichi; Kohara, Katsuhiko (Clinical endocrinology (Oxford), 2009)
The Ala allele of the Pro12Ala polymorphism (rs1801282) of peroxisome proliferator-activated receptor gamma (PPARgamma) is protective against type 2 diabetes (T2DM). Resistin, secreted from adipocytes, causes insulin resistance in rodents. Resistin gene expression is reduced by the PPARgamma ligand. We previously reported that subjects with the G/G genotype of a resistin gene single nucleotide polymorphism (SNP) at -420 (rs1862513) had the highest circulating resistin levels, followed by C/G and C/C. The aim of this study was to determine the relationship among PPARgamma Pro12Ala polymorphism, resistin SNP-420, and plasma resistin. We cross-sectionally analysed 2077 community-dwelling subjects attending an annual medical check-up. Genotypes were determined by TaqMan analysis. Fasting plasma resistin was measured using ELISA. Plasma resistin appeared to be higher in subjects with the Pro/Pro genotype of PPARgamma than those with Pro/Ala and Ala/Ala genotypes (mean +/- SE, 11.6 +/- 0.2 vs. 10.4 +/- 0.5 microg/l). Multiple regression analysis, adjusted for age, gender, BMI, and resistin SNP-420, revealed that the Pro/Pro genotype was a positive predictor of plasma resistin (PPARgamma , Pro/Pro vs. Pro/Ala + Ala/Ala, unstandardized regression coefficient (beta) = 1.03, P = 0.0384). The effects of the Pro/Pro genotype of PPARgamma (Pro/Pro vs. Pro/Ala + Ala/Ala) and the G/G genotype of resistin SNP-420 (G/G vs. C/C) on plasma resistin were synergistic (beta = 4.76, P = 0.011). The PPARgamma Pro12Ala Pro/Pro and resistin SNP-420 G/G genotypes were synergistically associated with plasma resistin, when adjusted for age, gender, and BMI, in the Japanese general population.